2021
DOI: 10.3389/fnagi.2021.721780
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Integrated11C-Pittsburgh Compound B Positron Emission Tomography/Magnetic Resonance for Cerebral Amyloid Angiopathy: A Pilot Study

Abstract: Objective: We aimed to compare amyloid deposition at the lobar cerebral microbleed (CMB) sites of cerebral amyloid angiopathy (CAA), Alzheimer’s disease (AD), and cognitively normal healthy controls (NC) and to propose a novel diagnostic method for differentiating CAA patients from AD patients with integrated 11C-Pittsburgh compound B (PIB) positron emission tomography (PET)/magnetic resonance (MR) and assess its diagnostic value.Methods: Nine CAA, 15 AD patients, and 15 NC subjects were enrolled in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Similarly, Dierksen et al [17] reported an elevated occipital-to-global ratio for CAA patients compared to AD patients. In this scenario Chang et al [41] reported lower global cortical 11 C-PIB uptake for CAA patients compared to AD, however, tracer uptake in occipital regions was higher in CAA compared to AD patients. In contrast, AD subjects had higher lateral temporal lobe deposition of tracer.…”
Section: Differential Diagnosis Between Caa and Admentioning
confidence: 77%
See 3 more Smart Citations
“…Similarly, Dierksen et al [17] reported an elevated occipital-to-global ratio for CAA patients compared to AD patients. In this scenario Chang et al [41] reported lower global cortical 11 C-PIB uptake for CAA patients compared to AD, however, tracer uptake in occipital regions was higher in CAA compared to AD patients. In contrast, AD subjects had higher lateral temporal lobe deposition of tracer.…”
Section: Differential Diagnosis Between Caa and Admentioning
confidence: 77%
“…Similarly, Gurol et al [19] confirmed this correlation with new bleeds, reporting that increased tracer retention characterized sites of future bleeds and a higher risk of incidental bleeds. Again, Chang et al [41] reported higher SUV values in CMB area of patients with CAA compared with those of AD or healthy subjects. In this setting Ly et al [18] reported increased 11 C-PIB uptake in patients with CAA-related hemorrhage (CAAH) and higher binding of tracer in patients with probable CAAH compared to patients with possible CAAH.…”
Section: Correlation With Cmb and Differential Diagnosis Of Ichmentioning
confidence: 96%
See 2 more Smart Citations
“…Detecting the cerebrovascular Aβ pathology is a crucial endpoint with diagnostic value and potential for monitoring CAA progression. In recent years, the development of positron emission tomography (PET) radiotracers for Aβ imaging (Farid et al, 2017;Chang et al, 2021) and cerebrospinal fluid (CSF) biomarkers (Kuiperij et al, 2020) have been an intensive focus of research in Allelic distribution of the SNPs associated with the CAA-SVD burden score using the common dominant model. The genetic risk factor (presenting or not the minor allele) associated with a higher score is represented in dark gray, whereas the protective factor is represented in light gray.…”
Section: Discussionmentioning
confidence: 99%